Range Extension of Ciliate Blue Anthene emolus Godart (Lepidoptera: Lycaenidae) and Blank Swift Caltoris kumara Moore (Lepidoptera: Hesperiidae) into the Lower Western Himalaya - Kumar, Shankar; Singh, Paramjit; Singh, Raj Shekhar (Journal of the Bombay Natural History Society (JBNHS), 2018)
No Abstract.